HUBUNGAN LINGKUNGAN BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA SEMESTER 4 PROGRAM STUDI KEBIDANAN D3 STIKES HARAPAN BANGSA PURWOKERTO - Wilis Sukmaningtyas (Viva Medika, 2016)
Learning achievement is the main yardstick to determine the success of one's learning. Thelearning achievement can also be used as an indicator of the quality of education. One of theinternal factors that affect the learning achievement is Emotional Intelligence, and one of herexternal factor is the learning environment.The purpose of this study was to determine the relationship of emotional intelligence and learningenvironment with students' achievement.This study uses correlation analysis, the population in this study is the fourth semester students ofmidwifery D3 STIKES Harapan Bangsa Purwokerto, the sample used is total sampling. Instrumentin this study was a questionnaire of emotional intelligence and learning environment, while usingthe tool ukut GPA student learning achievement. The analysis is the analysis of univariate andbivariate analysis with simple linear regression.The results showed that there was a relationship learning environment with students' achievementas indicated by p value (0.000). Keywords: Learning Environment, Achievements, GPA